The Temple in the Christian Bible - Stephen L. Cook (St Andrews Encyclopaedia of Theology, 2023)
The temple of Jerusalem was a monumental structure of the Middle East from the tenth century BCE until the year 70 CE. It passed through phases of renovation, demise, and reconstruction. In scripture, and in the faiths of Judaism and Christianity, the Jerusalem temple is more than merely a significant architectural monument. It expresses and instantiates an intersection of the transcendent and the terrestrial spheres. In the hermeneutical studies of the premodern church, for example, the temple is (1) the mystical ‘body’ of all God’s faithful people (the temple’s ‘allegorical’ sense), (2) the faithful soul of each genuine believer (the temple’s ‘tropological’ sense), and (3) the centre of God’s eschatological reign on Earth (the ‘anagogical’ sense). Scriptural warrants underlie all three senses. In Deuteronomy, God’s one shrine summons God’s one people to assemble in awe and joy before the one God (sense 1). In the Psalms, each individual pilgrim ascends Mount Zion in a liturgical reception of God’s imputed righteousness (sense 2). Isaiah and Micah envision the Mount of the Lord’s house raised as the highest mountain and all the Earth’s nations gazing upon it with joy (sense 3). The meaning and power of the temple proved highly expansive over time, growing through the pages of scripture to become a central biblical symbol, a ‘sacrament’, and a prophecy of God’s future kingdom, where deliverance flows out to all who are trapped in this disordered and troubled world. Isaiah the prophet, in chapter 6, glimpses the transcendent meaning of the temple, which the hem of God’s robe filled. He perceived it as a microcosm of the world, with God reigning from beyond the firmament (symbolized by the olivewood doors to the inner sanctuary), seated above the sky (symbolized by the altar’s clouds of incense). The prophet hears the seraphim call to one another, ‘[t]he whole earth is full of his glory’ (kābôd, Isa 6:3), whereas, in fact, it is the temple building alone that fills with the glory (kābôd). In affirming that the whole world is full of yhwh’s splendour, Isa 6:3 anticipates the assumption of Isa 66:1 that temple furnishings and iconography represent inklings of God’s cosmic habitation. Likewise, it anticipates the prayer of Ps 72:19 that the kābôd may someday fill the Earth and be seen by all flesh everywhere (see Isa 40:5).